Theology for ministry : an introduction for lay ministers - Hahnenberg, Edward P. (Collegeville, Minnesota : Liturgical Press, 2014)
"Theology for Ministry is for beginning ministry students, seasoned lay leaders, and anyone in between who wants to learn more about the faith that feeds their call to serve. Six easy-to-read chapters introduce the main areas of theology that every lay minister ought to know: the notion of vocation, the doctrine of God, Jesus Christ, the Holy Spirit, church, and ministry." -- Back cover
Called ... -- By God ... -- Through Christ ... -- In the Spirit ... -- With others ... -- For others.
Includes bibliographical references (pages 130-133).
Description based on print version record.
Keywords: Catholic Church -- Doctrines; Lay ministry -- Catholic Church; Laity -- Catholic Church; Catholic Church; Laity -- Catholic Church; Lay ministry -- Catholic Church; Theology, Doctrinal; RELIGION / Christian Theology / Ecclesiology; Electronic books